The role of christian education values as a moral defense to resolve a child sexual abuse phenomenon in Indonesia - Sahertian, Novita Loma; Metehoky, Benjamin; Ming, David (Universitas Jambi, Indonesia, 2025)
This research seeks to identify the effects of child sexual abuse and ways to address it. The following outline provides the answers: (1) Impact of Child Sexual Abuse: Children may suffer both physically and psychologically. Physical impacts include trauma to the genital area, sexually transmitted infections, and eating disorders. Psychological effects include depression, anxiety, post-traumatic stress disorder (PTSD), disturbances in eating and sexual behavior, loss of trust in adults, a sense of powerlessness, and stigmatization. (2) Efforts to Address Abuse: Multiple stakeholders are involved in addressing child sexual abuse, such as counselors, parents, schools and legal institutions. (3) Legal Action as Social Engineering: Legal measures can serve as tools for social transformation by producing and enforcing laws that promote social justice. These legal instruments must be understood, respected, and supported by society. Legislators must uphold the integrity of the law, free from external influence, and involve interdisciplinary perspectives in the development of legal frameworks.